2020
DOI: 10.1108/jica-09-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

Older people's perspectives on living in integrated housing and care settings: the case of extra care housing

Abstract: PurposeThis paper explores residents' perceptions and experiences of extra care housing as an integrated model of housing with care.Design/methodology/approachData were collected in a longitudinal qualitative study based on four extra care housing schemes. Data from interviews with residents, care workers, managers and local commissioners were analysed thematically.FindingsThe integration of housing with care enabled many older people to manage their care proactively. However, the increasing number of resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Two articles were based on a research study conducted in assisted living settings in Missouri, USA (Aud, 2002, 2004). Two articles were based on the Provision of Social Care in Extra Care Housing study (ECHO) conducted in England, UK (Cameron et al., 2020; Evans et al., 2020). Two articles were based on the Technology‐Enriched Supported Accommodation study conducted in Northern Ireland, UK (Rondon‐Sulbaran, Daly‐Lynn, McCormack, Ryan, & Martin, 2020, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles were based on a research study conducted in assisted living settings in Missouri, USA (Aud, 2002, 2004). Two articles were based on the Provision of Social Care in Extra Care Housing study (ECHO) conducted in England, UK (Cameron et al., 2020; Evans et al., 2020). Two articles were based on the Technology‐Enriched Supported Accommodation study conducted in Northern Ireland, UK (Rondon‐Sulbaran, Daly‐Lynn, McCormack, Ryan, & Martin, 2020, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Articles reporting a small amount of data (e.g. where people with dementia were a subgroup of the total sample) contributed least to the synthesis, regardless of methodological quality (Cameron et al., 2020; O’Malley et al., 2018; Stewart‐Archer et al., 2016). These articles still contributed meaningfully to the synthesis, as their participants included people with dementia (O’Malley et al., 2018; Stewart‐Archer et al., 2016) and their supporters (Cameron et al., 2020), with a limited amount of data available for these participant groups in the included articles.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, further investment in provision and more understanding of how to balance the expectations of residents with different needs will be necessary to support increasing levels of physical and cognitive frailty. Otherwise, extra care housing may become unviable for residents receiving publiclyfunded social care (Cameron et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…This study also investigated the profile of care staff working in AL SIH facilities, and found that despite residents having considerable care needs, 60% of staff had limited formal training in caring for older people with complex needs. Cameron et al's (2020) qualitative study of residents' experiences of living in EC SIH agreed, concluding that many residents, as well as staff, were concerned that staff could not cope with some of the additional needs that residents often experienced as their health and function declined over time. This precipitated moves to more intensive care support.…”
Section: Health and Wellbeing Characteristics Of Older People While Living In Sihmentioning
confidence: 99%
“…most SIH facilities) struggle to adequately address the needs of residents with complex health challenges and high dependency. Cameron et al's (2020) qualitative study of residents' experiences of living in EC SIH agreed, concluding that many residents, as well as staff, were concerned that staff could not cope with some of the additional needs that residents often experienced as their health and function declined over time. This precipitated moves to more intensive care support.…”
Section: Factors Influencing Moves Out Of Service-integrated Housingmentioning
confidence: 99%